High temperature fuel impacts on combustion characteristics of a swirl-stabilized combustor. (1st March 2023) - Corporan, Edwin; Williams, Veronica; Stouffer, Scott; Hendershott, Tyler; Monfort, Jeff
Highlights: Fuel temperature impacts on emissions and performance of a research combustor were assessed. Four fuels with a wide range properties were injected in the combustor up to 260 °C. Reductions in UHC, CO and PM emissions were observed as fuel temperatures increased. Lower radiation flames were observed in the primary zone with higher fuel temperatures. Slight suppression in combustor acoustic response resulted with higher fuel temperatures. Abstract: Future aircraft will require advanced thermal management systems to manage the increased heat loads resulting from the avionics, turbomachinery and other subsystems of higher performance, and high speed flight systems. Fuel is the primary coolant to alleviate these thermal management challenges. Heated fuel entering the combustor is likely to affect combustion performance due to dramatic changes in properties that impact fuel atomization, distribution, vaporization and fuel/air mixing. In this study, the combustion performance, emissions, and flame characteristics of a single-nozzle, swirl-stabilized combustor operating with high temperature fuels were investigated. Four fuels representing a wide range of jet fuel physical and chemical properties were studied at injection temperatures of 32, 121 and 260 °C. The test fuels included a conventional Jet A (A-2), a low cetane number alcohol-to-jet (ATJ) alternative fuel (C-1), n -dodecane (n-C12 ) and a high viscosity jet fuel blend (C-3A). Tests were conducted at a combustor pressure of 2 atm and inlet air temperature of 121 °C at global equivalence ratios (ϕ) of 0.10–0.24 for most fuel temperatures. Particulate matter (PM) emissions (concentrations and size distributions), and primary gaseous emissions were measured. High frequency pressure measurements and high-speed video were collected to assess fuel temperature impacts on combustion stability and flame characteristics, respectively. Results show that the heated fuel impacts on combustion were highly dependent on fuel type, temperature and ϕ. Qualitative results show that as fuel temperature increased, the flame in the primary zone appeared more compact, and less thermally radiant (lower soot). PM emissions were significantly impacted with reductions exceeding 95 % in particle number density for all fuels, and between 20 and 55 % reductions in mean particle diameters for aromatic-containing fuels. Gaseous emissions show up to ∼ 90 % reduction in unburned hydrocarbons (UHC) and up to 60 % reduction in carbon monoxide (CO), and corresponding moderate increases in NOx and CO2 with the heated fuel. The combustor acoustic response was slightly suppressed in frequencies of interest as fuel temperature increased. In general, the impacts of heated fuel on combustion were mostly beneficial and are primarily attributed to improved fuel atomization and reduced fuel evaporation timescales of the heated fuel. Specific impacts of fuel physical and chemical properties, and potential implications of heated fuel combustion are discussed.